Calcium signalling in weeds under herbicide stress: An outlook - Hamouzová, Katerina; Sen, Madhab Kumar; Bharati, Rohit; Košnarová, Pavlína; Chawdhery, Md Rafique Ahasan; Roy, Amit; Soukup, Josef (Frontiers in Plant Science, 2023)
The continuous use of herbicides for controlling weeds has led to the evolution of resistance to all major herbicidal modes of action globally. Every year, new cases of herbicide resistance are reported. Resistance is still in progress in many species, which must be stopped before it becomes a worldwide concern. Several herbicides are known to cause stressful conditions that resemble plant abiotic stresses. Variation in intracellular calcium (Ca2+) concentration is a primary event in a wide range of biological processes in plants, including adaptation to various biotic and abiotic stresses. Ca2+ acts as a secondary messenger, connecting various environmental stimuli to different biological processes, especially during stress rejoindering in plants. Even though many studies involving Ca2+ signalling in plants have been published, there have been no studies on the roles of Ca2+ signalling in herbicide stress response. Hence, this mini-review will highlight the possible sensing and molecular communication via Ca2+ signals in weeds under herbicide stress. It will also discuss some critical points regarding integrating the sensing mechanisms of multiple stress conditions and subsequent molecular communication. These signalling responses must be addressed in the future, enabling researchers to discover new herbicidal targets.